ANALISIS PERBANDINGAN SERANGAN HYDRA, MEDUSA DAN NCRACK PADA PASSWORD ATTACK - Dewa Made Julijati Putra; I Nyoman Namo Yoga Anantra; Putu Adhitya kusuma; Putu Damar Jagat Pratama; Gede Arna Jude Saskara; I Made Edy Listartha (Program Studi Informatika Universitas Teknologi Sumbawa, 2022)
An important aspect of a computer device is a security system, this security is made to protect the data inside so that it is not easily stolen by other people. Security systems owned by computer devices must be developed so that data remains safe from attacks. Several types of password attacks that are usually aimed at passwords are brute-force attacks, dictionary attacks, and hybrid attacks. In this research, we will focus on brute-force attacks. Brute-force attacks consist of an attacker sending many passwords or passphrases in the hope of guessing. correctly. The attacker systematically checks all possible passwords and passphrases until the right one is found. Or the attacker can try to guess the key which is usually generated from the password using the key derivation function. This is known as a complete key lookup. To make it easier to operate the brute-force attack will use the Kali Linux operating system. In this study we will use passwords that have been obtained and stored in file.txt, the tools that will be used in carrying out the attack are Hydra, Medusa, and Ncrack.